Lysine promotes proliferation and β-casein synthesis through the SLC6A14-ERK1/2-CDK1-mTOR signaling pathway in bovine primary mammary epithelial cells. (December 2022) - Cao, Yu; Hu, Guiqiu; Li, Wen; Wang, Jiaxin; Ge, Yusong; Li, Feng; Guo, Wenjin; Kan, Xingchi; Fu, Shoupeng; Liu, Juxiong
Abstract: Lysine, as the first limiting amino acid in dairy cows, has been shown to play an important role in milk synthesis and cell proliferation. However, the underlying mechanism remains unclear. In this study, we isolated bovine primary mammary epithelial cells (BMECs) and studied the mechanism in which lysine promotes cell proliferation and β-casein synthesis through overexpression and knockdown of CDK1 and supplements BCH, U0126, and rapamycin in BMECs. Results show that 0.7 mM lysine can significantly promote cell proliferation and the synthesis of β-casein in BMECs. In addition, lysine activates the ERK signaling pathway to promote the expression of CDK1. Further studies have shown that CDK1 can promote cell proliferation and the synthesis of β-casein through the mTOR signaling pathway in BMECs. Lastly, lysine can promote cell proliferation and the synthesis of β-casein through SLC6A14 in BMECs. The above results indicate that lysine promotes cell proliferation and the synthesis of β-casein through the SLC6A14-ERK-CDK1-mTOR signaling pathway in BMECs. Graphical abstract: Lysine promotes proliferation and β-casein synthesis through the SLC6A14-ERK-CDK1-mTOR signaling pathway in BMECs. Image 1 Highlights: Lysine increases β-casein synthesis and cell proliferation in BMECs. CDK1 promotes the cell proliferation and the synthesis of β-casein in BMECs. Lysine promotes cell proliferation and β-casein synthesis via CDK1.